Analisis Alih Kode dan Campur Kode pada Novel “Selamat Tinggal Pagi Selamat Datang Senja” Karya Anif Khasanah - Mila Indriati; Ita Kurnia; Frisca Verina Putri; Salsabilla Putri Amalia Ilmi (Khirani: Jurnal Pendidikan Anak Usia Dini, 2023)
This research was conducted to analyze the forms of code-switching and code-mixing in Anif Khasanah's novel Selamat Tinggal Pagi Selamat Datang Senja. The purpose of this research is to explain the use of code switching and code mixing in the novel Selamat Tinggal Pagi Selamat Datang Senja. This research succeeded in explaining that there was code switching in the form of Indonesian into Javanese, translating Indonesian into English, Indonesian into Arabic. The background of this code switching is the speaker and listener. Not only code switching, there is also code mixing in the form of words, code mixing in the form of clauses and code mixing in the form of phrases. Factors that cause code-mixing in the novel Selamat Tinggal Pagi Selamat Datang Senja are the desire to explain the identity of the variety, and change the topic of conversation. Keywords: code switching; code mixing